Measurement of the CP-violating phase s in the decay Bs0→J/ψ - Aaij, R; Abellan Beteta, C; Abellan Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Alkhazov, G; et al. (2012)
We present a measurement of the time-dependent CP-violating asymmetry in Bs0→J/ψ decays, using data collected with the LHCb detector at the LHC. The decay time distribution of Bs0→J/ψ is characterized by the decay widths Γ H and Γ L of the heavy and light mass eigenstates, respectively, of the Bs0-B̄s0 system and by a CP-violating phase s. In a sample of about 8500 Bs0→J/ψevents isolated from 0.37fb -1 of pp collisions at √s=7TeV, we measure s=0.15±0.18(stat)±0.06(syst)rad. We also find an average Bs0 decay width Γ s (Γ L+Γ H)/2=0.657±0.009(stat)±0.008(syst)ps -1 and a decay width difference ΔΓ s Γ L- Γ H=0.123±0.029(stat)±0.011(syst)ps -1. Our measurement is insensitive to the transformation ( s, ΔΓ s) (π- s,-ΔΓ s). © 2012 CERN. Published by the American Physical Society under the terms of the Creative Commons Attribution 3.0 License. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI.